Coupling coordination relationship between health resource allocation and regional economic development: an empirical study based on five provinces in eastern China - Wang, Yongqiang; Feng, Xiaochen; Chai, Yulin; Chen, Kexuan; Yang, Shilan; Li, Wei; Mi, Yuqing (Frontiers in Public Health, 2024)
BackgroundImproving system coordination is a pivotal strategy and a critical pathway for social governance. Chinese society is currently facing a significant challenge in aligning the allocation of health resources with economic development. Evaluating the level of coordinated development within the system can provide valuable insights to support the construction of a more coordinated China and foster high-quality development.MethodsBased on a systematically constructed indicator framework, our study selected data from five eastern provinces of China to establish a ten-year panel dataset covering the period from 2011 to 2020. The comprehensive evaluation index and the relative development degree were employed to comprehensively evaluate the development level of the system. The coupling coordination degree model was applied to analyze the coupling coordination relationship and spatiotemporal evolution trend of the two systems. Additionally, the fixed effects model was used to identify the driving factors behind the coordinated development of the two systems.ResultsFrom 2011 to 2020, the comprehensive indices of health resource allocation and economic development in the five eastern provinces of China exhibited a consistent year-on-year increase, and the relative development degree experienced two critical values of 0.8 and 1.2, which changed from the lagging allocation of health resources to the lagging economic development. The system coordination index generally ranged between 0.35 and 0.90, with the coordination phase undergoing a transition from an antagonistic stage to a coordinated stage. The coordination type also gradually shifted from mild imbalance to good coordination. Furthermore, the levels of economic development, economic structure, technological investment, as well as the allocation of health human and material resources, all serve as critical drivers in enhancing the coordinated development of the system.ConclusionThe coordinated development of eastern China’s provinces produces substantial spillover effects, and the realization of a Healthy China initiative must strategically harness their radiative and demonstrative effects. Achieving a superior level of coordination requires urgent efforts to rectify the existing deficiencies in the distribution of grassroots healthcare resources. Furthermore, cultivating innovative drivers of economic growth and enhancing the capacity for economic support are critical to ensuring high-quality and sustainable development.